2013
DOI: 10.4236/ajps.2013.412295
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of High Temperature during Growing Season on Potato Cultivars with Different Response to Environmental Stresses

Abstract: Potato crop is the fourth main food crops in the world after maize, rice and wheat. It is characterized by specific temperature requirements and develops best at about 20˚C. Forecasts of global warming prompt us to study the tolerance of potato genotypes to heat during the growing season. The aim of this work was to assess the response of chosen potato cultivars to high temperature during the different stages of plant growth under conditions of good soil moisture and drought. The impact of high temperature 32˚… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
44
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 14 publications
10
44
0
6
Order By: Relevance
“…The reaction of plants under conditions of increasing drought was significantly weaker (Figure 2). The results are consistent with the results of previous studies whereby a temperature higher than optimal intensified development of the aboveground part of plants (Rykaczewska 2013b(Rykaczewska , 2015. Heat stress under drought conditions negatively influenced PI activity in the tested plants.…”
Section: Resultssupporting
confidence: 92%
“…The reaction of plants under conditions of increasing drought was significantly weaker (Figure 2). The results are consistent with the results of previous studies whereby a temperature higher than optimal intensified development of the aboveground part of plants (Rykaczewska 2013b(Rykaczewska , 2015. Heat stress under drought conditions negatively influenced PI activity in the tested plants.…”
Section: Resultssupporting
confidence: 92%
“…1, Tables 4 and 5). The results are consistent with the results of previous studies whereby a temperature higher than optimal intensified development of the aboveground part of plants (Bodlaender 1963;Benoit et al 1983;Struik et al 1989a;Gawrońska et al 1992;Kooman and Haverkort 1995;Van Dam et al 1996;Rykaczewska 2013b). Our work additionally shows that the increase in plant height was greater the earlier they were exposed to heat.…”
Section: Height Of Plants and Chlorophyll A Fluorescence In Leaves Imsupporting
confidence: 83%
“…In the control there were no the tubers with physiological defects. Results of the experiment obtained by Rykaczewska (2013b) are similar. However, Levy (1985) show that a single treatment of high temperatures during early stages of tuber development caused a lower percentage of misshapen tubers.…”
Section: Tuber Physiological Defectssupporting
confidence: 76%
See 1 more Smart Citation
“…It is connected with the fact that temperature higher than optimal intensified development of the aboveground part of plants and tuberisation is significantly inhibited (Lafta and Lorenzen 1995). This is confirmed by the results of our previous studies, where it was found that under higher temperature the plants of all cultivars responded with an increase in height (Rykaczewska 2013(Rykaczewska , 2015.…”
supporting
confidence: 79%